"My body was telling me the direction:" The bodily dimension in the dance/movement therapists' working experiences. (November 2018) - Gross-Cohen, Iris; Eisikovits, Zvi
Highlights: The findings reveal a variety of personal experiences of DM therapists, condensed under the following aspects: The belief that the bodily dimension is a transformative means by being a vehicle for change. The belief in the dialectics between knowing and doing in therapy. The impact of the bodily dimension on the self. Abstract: This is a qualitative study of the physical dimension of the experience of being a dance/movement therapist as described by the therapists. The existential phenomenological approach underlies the conceptual framework of this study. The research population comprised the first author—a dance/movement therapist—and 10 of her peers. Two means of data collection were employed: Auto-ethnography and qualitative in-depth interviewing. The data collection consisted of self-documentation of the researcher's professional activities over time and 10 in-depth interviews conducted individually. Interpretative phenomenological analysis was performed. The major theme emerging from the data, "My body was telling me the direction" includes the various aspects of the bodily dimension in the dance/movement therapist's work. The findings are discussed in light of the suggested theoretical framework. Implications for doing therapy are addressed throughout.